PENERAPAN HIDROPONIK DAN PASCAPANEN SAYURAN PADA ORANGTUA SISWA SDN KARANGSALAM KABUPATEN BANYUMAS - Ahmad Fauzi; Prita Sari Dewi; Wilis Cahyani; Sapto Nugroho Hadi (LP2M Universitas Hasanuddin, 2021)
Abstract. Community service activities in the form of application of cultivation techniques and post-harvest processing of vegetable crop into healty and nutritious food products with the target of elemetary school students were proven to be able to increase: student’s interest, knowledge, and skills towards vegetable farming activities; consumption frequency of vegetable-based food; knowledge of various types of vegetables dan their benefits. The activitis need to be transmitted to the parents to solve problems: the habit of parents preparing instant foods that are minimal vegetable content for their children’s breakfast; the lack of parental knowledge in processing vegetabales to a variety of foods that are preferred by the children; limited knowledge about vegetables benefit for children growth and development; and house environment have not been used optimally for vegetable cutivation. The purpose of this activity were: training on vegetable cultivation techniques using two different hydroponic system (NFT and wick system); post-harvest knowledge transfer of vegetable into preferred foods for the children; knowledge transfer about the importance of vegetables for childern growth and development. The method implemented in this activity were making demonstration and plot (demplot) of NFT dan wick system; vegetable cultivation activities through direct practice; post-harvest knowledge transfer of vegetable into preferred foods for the children; transfer of knowledge about healthy food with balanced nutrition to support the growth and development of school-age children. As a result, all activities are going well with high target audience participation. Hydroponic demonstration plots are prepared to produce crops of kale, spinach, pakcoy up to four times. Through this activity, parents' knowledge and skills have increased in: cultivation of vegetable plants using hydroponic techniques; postharvest processing of vegetable products into foods that children like; knowledge of the importance of the benefits of vegetables for children. Abstrak. Kegiatan pengabdian kepada masyarakat berupa aplikasi budidaya dan pameran produk makanan berbasis sayuran dengan khalayak sasaran siswa sekolah dasar terbukti mampu meningkatkan ketertarikan, pengetahuan, dan keterampilan siswa terhadap kegiatan bertanam sayuran; frekuensi konsumsi makanan berbahan sayuran; pengetahuan ragam jenis sayur dan manfaatnya. Kegiatan perlu diterapkan lebih luas kepada orang tua siswa untuk mengatasi permasalahan kebiasaan orang tua menyiapkan makanan instan yang minim sayur untuk anaknya; minimnya pengetahuan orang tua dalam melakukan kegiatan pengolahan tanaman sayuran menjadi aneka makanan yang disukai anak-anak; terbatasnya pengetahuan pentingnya manfaat sayuran bagi anak usia sekolah, dan; belum termanfaatkannya lingkungan rumah untuk kegiatan bertanam sayuran. Tujuan kegiatan ini adalah memberikan pengetahuan dan keterampilan kepada orang tua siswa SDN Karangsalam melalui pelatihan teknik budidaya tanaman sayuran menggunakan teknik hidroponik NFT dan Wick system untuk pemanfaatan lahan pekarangan rumah; transfer pengetahuan pascapanen produk tanaman hasil panen menjadi produk makanan yang disukai anak-anak, dan; transfer pengetahuan pentingnya manfaat sayuran bagi pertumbahan dan perkembangan anak usia sekolah. Metode yang dilaksanakan dalam kegiatan pengabdian ini adalah metode partisipatif. Khalayak sasaran diajak berperan aktif dalam kegiatan pembuatan perangkat hidroponik tanaman sayuran; demplot hidroponik; kegiatan budidaya tanaman sayuran dengan praktik langsung; transfer pengetahuan pascapanen produk tanaman hasil panen menjadi produk makanan yang disukai anak-anak; transfer pengetahuan pentingnya manfaat sayuran bagi anak usia sekolah. Hasilnya, pengetahuan dan keterampilan orang tua meningkat dalam hal: budidaya tanaman sayuran menggunakan teknik hidroponik; pengolahan pascapanen produk sayuran menjadi makanan yang disukai anak-anak; dan pentingnya manfaat sayuran bagi anak-anak.